2010
DOI: 10.1007/s10585-010-9347-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fat on spontaneous metastasis of Lewis lung carcinoma in mice

Abstract: The present study assessed the effects of dietary fat on spontaneous metastasis of Lewis lung carcinoma in mice. Three-week old male C57BL/6 mice were fed the AIN-93G diet or a 45% fat diet (% kcal.) for 7 weeks before they were subcutaneously injected with 2.5 × 10⁵ viable carcinoma cells. The primary tumor was resected 2 weeks later, and mice were maintained on their respective diets for an additional 2 weeks. The high-fat diet significantly increased body weight and abdominal adipose weight compared to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 37 publications
(43 reference statements)
1
27
0
Order By: Relevance
“…Consumption of a high-fat diet increased adiposity and plasma levels of PAI-1, MCP-1, and TNF-α in non-tumor-bearing C57BL/6 mice (32), and obesity-enhanced metastasis is known to be accompanied by increases in plasma PAI-1 and MCP-1 (22). That high-fat feeding increased plasma concentrations of PAI-1, MCP-1, TNF-α, and leptin regardless of Se supplementation and that Se reduced plasma proteolytic proteases (uPA, MMP-9) and angiogenic factors (VEGF, TIMP-1) regardless of the type of diet suggest that adipose-derived inflammatory cytokines may be key determinants of the enhanced LLC aggression by high-fat feeding, which may overpower the inhibitory actions of Se on metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumption of a high-fat diet increased adiposity and plasma levels of PAI-1, MCP-1, and TNF-α in non-tumor-bearing C57BL/6 mice (32), and obesity-enhanced metastasis is known to be accompanied by increases in plasma PAI-1 and MCP-1 (22). That high-fat feeding increased plasma concentrations of PAI-1, MCP-1, TNF-α, and leptin regardless of Se supplementation and that Se reduced plasma proteolytic proteases (uPA, MMP-9) and angiogenic factors (VEGF, TIMP-1) regardless of the type of diet suggest that adipose-derived inflammatory cytokines may be key determinants of the enhanced LLC aggression by high-fat feeding, which may overpower the inhibitory actions of Se on metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, high expressions of PAI-1 (33,34), MCP-1 (35,36), TNF-α (37), uPA (34), MMP-9 (29,38), VEGF (38), and TIMP-1 (39) have been associated with regional or distant metastasis and poor prognosis in cancer patients. Elevations of those cytokines (40)(41)(42), proteases (43,44), and angiogenic markers (22,45) have been reported in animal models of various malignancies. The present results are consistent with the existing knowledge and prove the usefulness of the LLC model to study spontaneous metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that obesity and a high fat diet can enhance cancer metastases within the body as excess lipids can aggravate cancer (116,117). Using the novel imaging capabilities of CARS and other NLO techniques, one can provide novel insights into the dynamics and mechanisms of cancer invasion.…”
Section: Insight Into Mechanisms Of Tumour Invasion and Metastasesmentioning
confidence: 99%
“…The high dietary fiber in green leafy vegetables helps regulate the digestive system aiding bowel health and weight management. Several studies have shown that high folate intake from green leafy vegetables may lower the risk of colon polyps by 30 to 40 percent compared to low intake of this vitamin suggesting that diets low in folate may increase the risk of colon cancer [8,9]. Low folate intake has also been associated with cancers of the breast, cervix and lung.…”
Section: Introductionmentioning
confidence: 99%